Notas sobre la estructura de un grupo de Alouatta seniculus seniculus (Primates: Atelidae), en Limoncocha, Ecuador - Ramírez-Jaramillo, Salomón M.; Mesías, Alejandro; Andi-Grefa, Lizbeth C. (Neotropical Primates, 2024)
Population structure in primate groups in the Ecuadorian Amazon is little studied. The present observations occurred in Limoncocha, Sucumbíos province, Ecuador. We observed a group of red howlers (Alouatta seniculus), composed of nine individuals: three adult males, two adult females, two pregnant females and two juveniles, one of them male. The group was observed moving among the branches of the trees until they stopped in search of food and settled down to spend the night. In the place used as a sleeping site, adults fed on leaves while the juveniles played until 17h30 when they settled down for the night. By 7h30 the next morning the group had moved on to another location. Information on the group composition for A. seniculus in Amazonian Ecuador is scarce, so this observation contributes to our knowledge of it.